2011
DOI: 10.1213/ane.0b013e3182274803
|View full text |Cite
|
Sign up to set email alerts
|

Early Thoracic Sympathetic Block Improves the Treatment Effect for Upper Extremity Neuropathic Pain

Abstract: The results showed that an earlier TSB produced a better outcome for patients with chronic pain syndrome. Thus, early TSB should be performed in patients with chronic pain in the upper extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Several studies proved this hypothesis and showed dramatic improvement in pain relief after sympathetic blockage [37], sympathectomy [38], or temporary blockage with α -adrenergic antagonists with intravenous phentolamine [39]. …”
Section: Neuropathic Pain Generation Pathogenesismentioning
confidence: 99%
“…Several studies proved this hypothesis and showed dramatic improvement in pain relief after sympathetic blockage [37], sympathectomy [38], or temporary blockage with α -adrenergic antagonists with intravenous phentolamine [39]. …”
Section: Neuropathic Pain Generation Pathogenesismentioning
confidence: 99%
“…The symptoms of neuropathic pain are: allodynia (pain perception upon the innocuous tactile stimuli), hyperalgesia (exaggerated pain sensations by mildly noxious stimuli) and spontaneous pain with varying intensity. It is an obstacle in daily activities and can decrease quality of life considerably (Pickering et al, 2011;Treede et al, 2008;Xie et al, 2008;Yoo et al, 2011). The pathophysiology of neuropathic pain is complex.…”
Section: Introductionmentioning
confidence: 99%
“…In the preclinical and clinical studies, it was shown that early application of nerve block can prevent or reduce neuropathic pain. [10,11] Therefore, we decided to turn our therapeutic focus toward nerve block.…”
Section: Discussionmentioning
confidence: 99%